Effect of Crown Position on Cone, Seed and Germination Characteristics in Himalayan Cedar - Singh, Virendra; Lavania, S. K.; Sah , V. K. (Indian Forester, 2013)
The results of the study revealed that the cone length (11.54 cm), cone diameter (6.10 cm), number of fertile scales/cone (246.96), total number of scales/cone (282.28), number of seeds/cone (472.27) and weight of seeds/cone (71.50 g) were highest for the cones which were collected from upper crown. The seed length (15.45 mm), width (5.01 mm), thickness (3.50 mm), fresh (15.04 g) and dry weight of 100 seed (11.72 g) were also found maximum of those seeds which were extracted from the cones collected from upper crown. The maximum germination (64.00 %) was obtained from the seeds extracted from the cones collected from upper crown under laboratory condition and was significantly higher than the germination of seeds from middle crown and lower crown. The results of germination in nursery revealed almost the same trend but the values of different parameters were less than the values obtained under controlled conditions.